ORGANISATIONAL CHANGE: THE IMPACT OF RESTRUCTURING ON SUNWAY COLLEGE KUALA LUMPUR EMPLOYEES - Ismail, Noorwati; Sani, Asreen Ayumi Abdullah; Zolkafle, Ernee; AbuBaker, Reem Abbas (IIUM Journal of Case Studies in Management, 2014)
Organisational change could affect the organisation positively or negatively. Apart from the management, employees are also affected with the changes. In the case of Sunway College Kuala Lumpur (SCKL), the organisational restructuring involves an establishment of new companies where the employees are realigned and transferred to different companies. The purpose of this case study is to identify the issues faced by the SCKL employees after the restructuring and how the management is handling these issues. The information is gathered through in-depth interviews with the employees under SCKL and Sunway Education Group Sdn Bhd, as well as the students who are under the Australian University Programme. Based on the findings, the management perceives the issues raised by the employees as mere perception, and instead claims that the restructuring has actually had a positive impact. We have further analysed the issues and integrated our findings with the management theories discussed in the Organizational Behaviour and Leadership course. However, we note that the information collected is prone to bias due to the limited number of respondents interviewed.